Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Pada Industri Manufaktur Dimediasi Pengembangan Karyawan - Nelson, Alden; Vangoh, Irene (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The research aims to analyze factors that influence employee performance mediated by employee development. The number of respondents was 470 employees who worked in manufacturing companies in the Batam area. Data analysis uses the Structural Equation Modeling (SEM)-SmartPLS method. The research results show that talent management, employee appreciation and knowledge management have an influence on employee performance. In addition, employee development has been proven to have an influence as a mediator between talent management and employee performance, but employee development variables cannot mediate between employee appreciation and knowledge management on employee performance. Companies can improve knowledge management by providing facilities for employees to increase their knowledge, and also implementing incentives for employees who excel as part of employee development to maximize employee performance. Keywords: employee performance, knowledge management, talent management, employee development, employee rewards